Dehydration of Glucose to 5-Hydroxymethylfurfural Using Combined Catalysts in Ionic Liquid by Microwave Heating. Issue 11 (1st November 2016) - Wang, Pan; Ren, Lianhai; Lu, Qingyu; Huang, Yanbing
Abstract : The dehydration of glucose into 5-hydroxymethylfurfural (HMF) was catalyzed by NKC-9 (a macroporous sulfonated polystyrene ion-exchange resin) combined with metal oxides (TiO2, ZrO2, Al2 O3 calcined at different temperatures). In the combined catalytic system, Al2 O3 calcined at 550°C exhibited excellent catalytic activity, when the dosage of NKC-9 was kept constant. Four parameters (catalyst dosage, reaction temperature, reaction time, and initial glucose amount) were optimized by employing response surface methodology (RSM), with HMF yield as the response parameter. The maximum HMF yield of 62.09% was obtained at catalyst 0.07 g, temperature 140°C, time 20 min, and glucose 0.01 g. The catalytic activity of the binary catalyst (NKC-9 and Al2 O3 ) for the conversion of glucose into HMF did not show significant decrease after five-times uses at 140°C for 20 min.